Response of Methanogenic Archaea from Siberian Permafrost and Non-permafrost Environments to Simulated Mars-like Desiccation and the Presence of Perchlorate - Serrano, Paloma; Alawi, Mashal; de Vera, Jean-Pierre Paul (Prof. Dr. rer. nat.); Wagner, Dirk (PD Dr. habil.) (Astrobiology, 2019)
Numerous preflight investigations were necessary prior to the exposure experiment BIOMEX on the International Space Station to test the basic potential of selected microorganisms to resist or even to be active under Mars-like conditions. In this study, methanogenic archaea, which are anaerobic chemolithotrophic microorganisms whose lifestyle would allow metabolism under the conditions on early and recent Mars, were analyzed. Some strains from Siberian permafrost environments have shown a particular resistance. In this investigation, we analyzed the response of three permafrost strains (Methanosarcina soligelidi SMA-21, Candidatus Methanosarcina SMA-17, Candidatus Methanobacterium SMA-27) and two related strains from non-permafrost environments (Methanosarcina mazei, Methanosarcina barkeri) to desiccation conditions (-80 degrees C for 315 days, martian regolith analog simulants S-MRS and P-MRS, a 128-day period of simulated Mars-like atmosphere). Exposure of the different methanogenic strains to increasing concentrations of magnesium perchlorate allowed for the study of their metabolic shutdown in a Mars-relevant perchlorate environment. Survival and metabolic recovery were analyzed by quantitative PCR, gas chromatography, and a new DNA-extraction method from viable cells embedded in S-MRS and P-MRS. All strains survived the two Mars-like desiccating scenarios and recovered to different extents. The permafrost strain SMA-27 showed an increased methanogenic activity by at least 10-fold after deep-freezing conditions. The methanogenic rates of all strains did not decrease significantly after 128 days S-MRS exposure, except for SMA-27, which decreased 10-fold. The activity of strains SMA-17 and SMA-27 decreased after 16 and 60 days P-MRS exposure. Non-permafrost strains showed constant survival and methane production when exposed to both desiccating scenarios. All strains showed unaltered methane production when exposed to the perchlorate concentration reported at the Phoenix landing site (2.4 mM) or even higher ...